1997
DOI: 10.1038/sj.leu.2400579
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of a 5′ CpG island of p16 is a frequent event in non-Hodgkin’s lymphoma

Abstract: Hypermethylation of a 5′ CpG island of p16 gene has been Materials and methodsrecently described as a possible way of inactivation of this tumor suppressor gene, alternative to deletions and mutations. Tumor samplesWe have investigated if hypermethylation of a 5′ CpG island of p16 occurs in non-Hodgkin's lymphoma (NHL) and normal A total of 82 lymphomas diagnosed were analyzed, according

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 3 publications
0
57
2
Order By: Relevance
“…22 The p16 INK4A gene is frequently methylated in non-Hodgkin's leukemia, a malignancy common in AIDS patients. [31][32][33] Because these studies relied on an integrasedeficient HIV-1 strain (IN D116N ), integration into the host genome does not appear necessary to elicit these epigenetic changes. 22 This work also demonstrated that HIV-1 infection of T cells causes a ~4-fold increase in DNMT1 expression, without commensurate changes in the expression of DNMT3α or DNMT3β.…”
Section: Introductionmentioning
confidence: 99%
“…22 The p16 INK4A gene is frequently methylated in non-Hodgkin's leukemia, a malignancy common in AIDS patients. [31][32][33] Because these studies relied on an integrasedeficient HIV-1 strain (IN D116N ), integration into the host genome does not appear necessary to elicit these epigenetic changes. 22 This work also demonstrated that HIV-1 infection of T cells causes a ~4-fold increase in DNMT1 expression, without commensurate changes in the expression of DNMT3α or DNMT3β.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, gene methylation was a major occurrence among p16 gene alterations in our study, which is in accord with previous reports. [10][11][12][13][14][15][16] Gene deletion is another means of p16 gene silencing, but has been rare in MALT lymphomas. 32,33 We attempted to detect p16 gene deletions using seven microsatellite markers, 16,34 however, most of the cases were not amplifiable or informative.…”
Section: Discussionmentioning
confidence: 99%
“…p16 gene has been considered as a tumor-suppressor gene, and among CDK inhibitors, only p16 gene is frequently silenced in a variety of tumors by epigenetic or genetic abnormalities including promoter CpG methylation and less frequently, allelic loss and gene mutation. 10,11 In lymphoid malignancies, p16 gene silencing, mainly induced by gene methylation, is frequently found in Hodgkin and non-Hodgkin lymphomas, [12][13][14] and has been associated with tumor progression. [15][16][17][18][19] However, it has also been suggested that the methylation of this gene is one of the early events in the development of lymphoid malignancies.…”
mentioning
confidence: 99%
“…7 Previous reports have shown that inactivation of tumor suppressor genes by methylation is important in the development and malignant transformation of EMZLs. [8][9][10][11][12] However, because of its rarity, methylation studies have not been described in colorectal EMZLs.…”
mentioning
confidence: 99%